Iron-manganese binary compound precursor as well as preparation method and application thereof
The precursor of iron-manganese binary composite is prepared by co-precipitation reaction in ammonia water and mixed with lithium salt, phosphorus salt and carbon source, which solves the problems of high costs, difficulty in removing impurities and uneven element distribution in the prior art, and achieves efficient preparation of lithium iron-manganese phosphate/carbon composite materials, which is suitable for lithium-ion battery positive electrode materials.
Patent Information
- Application Number
- CN202510408759.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-07-11
AI Technical Summary
The prior art has problems such as high cost, high energy consumption, difficulty in removing impurities, and uneven distribution of elements in the process of preparing the precursor of the lithium iron manganese phosphate positive electrode material, which is difficult to meet the needs of industrial production.
The iron and manganese mixed metal salt solution was used to co-precipitate and react in ammonia water with carbonate or mixed alkali solution of bicarbonate and hydroxide, and the pH was controlled to be between 11.0 and 13.0. Then filtered, washed and dried to obtain an iron-manganese binary composite precursor, and mixed with lithium salt, phosphorus salt and carbon source. After spray drying and sintering, lithium iron-manganese phosphate/carbon composite material was prepared.
The prepared iron-manganese binary composite precursor has a large specific surface area, low impurity content and low cost. It is suitable for industrial production. The lithium iron-manganese phosphate/carbon composite material has excellent electrochemical performance and is suitable for use as the positive electrode material of lithium-ion batteries.
Smart Images

Figure CN120288827A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cathode materials for lithium-ion batteries, and particularly relates to an iron-manganese binary composite precursor, a preparation method thereof, and an application thereof. Background Art
[0002] Phosphate cathode materials have good thermal stability and structural stability, which makes them relatively safe under extreme conditions such as overcharge, over-discharge, and short circuit, reduces the risk of thermal runaway of the battery, has a relatively low cost, is conducive to large-scale production and application, and at the same time has good cycle stability, and can support the battery to maintain performance during multiple charge and discharge cycles. Preparing phosphate cathode materials with excellent performance requires the assistance of corresponding precursors with excellent performance. Therefore, how to prepare a suitable precursor has become an urgent problem to be solved in the whole industry. And lithium iron manganese phosphate, regarded as an upgraded version of lithium iron phosphate, the development of its corresponding precursor has also become extremely important.
[0003] Currently, a lot of work has been done on iron-manganese binary composite precursors. To achieve more excellent electrochemical performance, a manganese iron phosphate precursor that can achieve uniform distribution of phosphorus, manganese, and iron elements is highly favored. However, the intrinsic K SP values of iron phosphate and manganese phosphate differ greatly, and it is very difficult to co-precipitate to form a manganese iron phosphate precursor in a conventional liquid-phase reaction system. Although some technologies can succeed, for example, Chinese invention patent CN105244497A provides a preparation method of a manganese iron phosphate precursor, in which manganese iron phosphate precursor is co-precipitated by using iron nitrate and manganese nitrate in a water-ethanol mixed system. However, the large amount of use of nitrates and ethanol in the process leads to a high cost, and a large amount of waste water and waste acid are generated during the whole process, making it difficult to be applied to industrial production.
[0004] Binary precursors such as manganese iron oxalate and manganese iron carbonate have gradually started the industrialization process due to the similarity of their intrinsic K sp values of manganese and iron. However, their main contents of iron and manganese are relatively low, which will seriously affect the production capacity in industrial production; and a large amount of gas will be released during the sintering process, seriously damaging the tap density of lithium iron manganese phosphate.
[0005] The iron-manganese binary precursor can provide a high main content of iron and manganese, and no waste gas is generated during the mixing and sintering process. It is a promising precursor for iron-manganese binary composites. Chinese invention patent CN119118087A provides a preparation method of an iron-manganese oxide precursor: the iron-manganese oxide precursor is obtained by solid-phase mixing of an iron source, a manganese source, silicon dioxide, and a basic oxide followed by high-temperature sintering (200 - 900 °C). High-temperature sintering increases the processing cost of the precursor, and at the same time, it is difficult to ensure the atomic-level uniform mixing of iron and manganese elements during solid-phase mixing. Chinese invention patent CN119284859A provides a preparation method of an iron-manganese oxide precursor: a reaction mixture is obtained by simultaneously dropping a mixed solution of manganese and iron ions and a sodium hydroxide precipitant into a complexing agent bottom solution. After heat preservation and aging of the reaction mixture, solid-liquid separation is carried out to obtain a filter cake, and the filter cake is successively subjected to washing, drying, and calcination to obtain iron manganese oxide; however, this method also requires high-temperature calcination once, greatly increasing the energy consumption and processing cost during the preparation process. Chinese invention patent CN104868123A provides a preparation method of an iron-manganese oxide precursor: a sodium hydroxide precipitant is dropped into a mixed solution of manganese and iron ions, and heat preservation treatment is carried out at a certain temperature to obtain a suspension. Solid-liquid separation is carried out on the suspension to obtain a filter cake, and the filter cake is successively subjected to washing and drying to obtain iron manganese oxide; although this method can prepare iron-manganese oxides in one step in a liquid phase system and the process is relatively simple, the molar ratio of manganese to iron can only be fixed at 1:2, which has little industrial significance for the preparation of lithium iron manganese phosphate cathode materials that require a high manganese content to improve the energy density. In addition, during the preparation of an iron-manganese oxide precursor by liquid-phase coprecipitation using sulfates as raw materials, due to the high manganese content, primary particles often grow more closely, resulting in sulfate ions being easily wrapped between the precursor crystal layers during the reaction process and being difficult to remove during the subsequent washing process, leading to an irreversible decrease in the capacity and performance of the lithium iron manganese phosphate cathode material and affecting the safety performance of the subsequent battery. Summary of the Invention
[0006] To solve the deficiencies existing in the prior art, the present invention provides a precursor of an iron-manganese binary composite, its preparation method and application. The precursor of the iron-manganese binary composite and the lithium iron manganese phosphate / carbon composite material prepared by the preparation method of the present invention have a high specific surface area, low cost, adjustable iron-manganese ratio, low impurity content, simple production process, are suitable for industrial production, and have good electrochemical performance.
[0007] To achieve the above objectives, the technical solutions provided by the present invention are as follows:
[0008] In the first aspect, the present invention provides a preparation method of a precursor of an iron-manganese binary composite, including the following steps:
[0009] The iron and manganese mixed metal salt solution and the mixed alkali solution are simultaneously dropped into the ammonia water solution. After the dropping is completed, a coprecipitation reaction is carried out, followed by filtration, washing, and drying to obtain a binary iron-manganese composite precursor;
[0010] The mixed alkali solution is prepared by dissolving hydroxides and carbonates or bicarbonates in water;
[0011] The total concentration of the hydroxides and carbonates or bicarbonates is 4.0 mol / L - 10.0 mol / L; the molar ratio of carbonate or bicarbonate to the total iron and manganese metal elements in the mixed alkali solution is (0.4 - 0.9):1; the molar ratio of hydroxide to the total iron and manganese metal elements in the mixed alkali solution is (2.0 - 2.5):1; the concentration of the ammonia water solution is 5.35 - 13.38 mol / L, and the molar ratio of ammonia to the total iron and manganese elements is (0.5 - 1.5):1; the pH value of the coprecipitation reaction is 11.0 - 13.0.
[0012] Preferably, the molar ratio of carbonate or bicarbonate to the total iron and manganese metal elements in the mixed alkali solution is (0.5 - 0.8):1, and the molar ratio of hydroxide to the total iron and manganese metal elements in the mixed alkali solution is (2.1 - 2.5):1.
[0013] Further preferably, the molar ratio of carbonate or bicarbonate to the total iron and manganese metal elements in the mixed alkali solution is (0.5 - 0.6):1, and the molar ratio of hydroxide to the total iron and manganese metal elements in the mixed alkali solution is (2.2 - 2.5):1.
[0014] More preferably, the molar ratio of hydroxide to the total iron and manganese metal elements in the mixed alkali solution is (2.4 - 2.5):1.
[0015] Furthermore, in the iron and manganese mixed metal salt, the iron is a trivalent iron salt and the manganese is a divalent manganese salt.
[0016] Preferably, the iron salt is at least one of ferric nitrate, ferric sulfate, and ferric chloride, and the manganese salt is at least one of manganese chloride, manganese acetate, manganese sulfate, and manganese nitrate.
[0017] Furthermore, the total metal concentration in the iron and manganese mixed metal salt solution A is 0.5 mol / L - 5 mol / L, and the molar ratio of manganese to iron is x:(1 - x), where x is 0.5 - 0.9.
[0018] Furthermore, the carbonate is at least one of ammonium carbonate, ammonium bicarbonate, sodium carbonate, potassium carbonate, and sodium bicarbonate; the hydroxide is at least one of potassium hydroxide, sodium hydroxide, and ammonia water.
[0019] Further, the temperature of the coprecipitation reaction is 40°C - 70°C, and the time is 2 h - 8 h.
[0020] Preferably, the coprecipitation reaction is carried out under stirring conditions, and the stirring speed is 400 rpm - 800 rpm.
[0021] Further, for the simultaneous dropping, the dropping time is 15 min - 120 min; the dropping temperature is 20 - 30°C; for the washing, the conductivity of the filtrate after washing is lower than 300 μS / cm.
[0022] Further, the drying temperature is 80°C - 100°C, and the time is 8 - 12 h.
[0023] In a second aspect, the present invention provides a method for preparing a lithium iron manganese phosphate / carbon composite material, comprising the following steps:
[0024] S1. Mix and grind a binary iron-manganese composite precursor with a lithium salt, a phosphorus salt, and an additive in a liquid phase system, spray dry, and sinter in an inert atmosphere to obtain a prelithiated lithium iron manganese phosphate precursor;
[0025] S2. Take the prelithiated lithium iron manganese phosphate precursor obtained in step S1 and a carbon source, grind and mix them in a liquid phase system, and spray dry to obtain a lithium iron manganese phosphate / carbon composite material precursor;
[0026] S3. Sinter the lithium iron manganese phosphate / carbon composite material precursor obtained in step S2 in an inert atmosphere to obtain a lithium iron manganese phosphate / carbon composite material.
[0027] Further, in step S1, the lithium salt is at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.
[0028] Further, the phosphorus salt is at least one of ammonium dihydrogen phosphate, ammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, and lithium phosphate.
[0029] Further, the additive is at least one of titanium dioxide, tetrabutyl titanate, magnesium hydroxide, magnesium oxide, magnesium acetate, magnesium nitrate, zirconium dioxide, zirconium hydroxide, niobium pentoxide, nickel acetate, and nickel oxide.
[0030] Further, the addition amount of the additive is 0 - 1.0% of the mass of the prelithiated lithium iron manganese phosphate precursor.
[0031] Further, in step S1, the molar ratio of the lithium salt, the binary iron-manganese composite precursor, and the phosphorus salt is (1.1 - 1.0):1:(1.1 - 1.0); the sintering temperature in step S1 is 400 - 700°C, and the time is 2 - 6 h.
[0032] Further, the inert atmosphere is any one of nitrogen, argon, and helium.
[0033] Further, in steps S1 and S2, the liquid phase system is any one of water, ethanol, and methanol.
[0034] Further, in steps S1 and S2, the grinding is first coarse-ground to a particle size D 50 = 1 - 2 μm, and then fine-ground to a particle size of 300 - 500 nm.
[0035] Preferably, in steps S1 and S2, the inlet temperature of the spray drying is 250 - 270 °C, and the outlet temperature is 95 - 105 °C.
[0036] Further, the carbon source in step S2 is at least one of glucose, rock sugar, sucrose, fructose, polyethylene glycol, cyclodextrin, starch, and cellulose.
[0037] Further, the sintering temperature in step S3 is 675 - 780 °C, and the time is 4 - 10 h; the inert atmosphere is at least one of nitrogen, argon, and helium.
[0038] Further, the mass content of carbon in the lithium iron manganese phosphate / carbon composite material is 1.2% - 2.0%.
[0039] Preferably, the lithium iron manganese phosphate / carbon composite material is subjected to classification and crushing treatment with a classification frequency of 90 HZ.
[0040] In a third aspect, the present invention provides an application of a preparation method of an iron-manganese binary composite precursor and a preparation method of a lithium iron manganese phosphate / carbon composite material in reducing impurities in the iron-manganese binary composite precursor and the lithium iron manganese phosphate / carbon composite material.
[0041] In a fourth aspect, the present invention provides an iron-manganese binary composite precursor prepared by the above preparation method.
[0042] In a fifth aspect, the present invention provides a lithium iron manganese phosphate / carbon composite material prepared by the above preparation method.
[0043] In a sixth aspect, the present invention provides a battery, comprising the lithium iron manganese phosphate / carbon composite material prepared by the above preparation method.
[0044] The beneficial effects of the present invention are as follows:
[0045] 1) The preparation method of the present invention adds an iron and manganese mixed metal salt solution and a mixed alkali solution containing a carbonate or bicarbonate and a hydroxide solution into ammonia water simultaneously to carry out a coprecipitation reaction. The process is simple and low in cost. The prepared iron-manganese binary composite precursor has a large specific surface area, low impurity content and high activity. At the same time, the molar ratio of Fe / Mn can be adjusted during the whole preparation process, and the recovery rate of iron and manganese elements can be as high as 96%, which is suitable for industrialization.
[0046] 2) The present invention also provides a preparation method of a lithium iron manganese phosphate / carbon composite material; by mixing and sintering the iron-manganese binary composite precursor of the present invention with a lithium source, phosphoric acid and an additive, and then mixing and grinding the sintered precursor with a carbon source again and carrying out solid-phase sintering, a lithium iron manganese phosphate / carbon composite material with excellent electrical properties can be finally prepared. Brief Description of the Drawings
[0047] Figure 1 : SEM image of the lithium iron manganese phosphate prepared in Example 1.
[0048] Figure 2 : XRD pattern of the iron-manganese binary composite precursor prepared in Example 1.
[0049] Figure 3 : Discharge curve of the lithium iron manganese phosphate prepared in Example 1.
[0050] The present invention will be further described below in conjunction with the drawings and examples. Detailed Embodiments
[0051] The present invention will be described below through specific examples to make the technical solution of the present invention easier to understand and master, but the present invention is not limited thereto. The experimental methods described in the following examples are all conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified; and different sources do not have a significant impact on the product performance.
[0052] Example 1
[0053] Preparation of the iron-manganese binary composite precursor:
[0054] Dissolve 152.73 g of hydrated ferric sulfate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 137.49 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.2), 95.40 g of Na2CO3 (99%) (CO3 2-:(Total metal salts = 0.6:1) was dissolved in 750 mL of deionized water to obtain the first precipitant mixed alkali solution B. 56.26 mL of concentrated ammonia water (NH₃ content 25%) and 56.26 mL of pure water were weighed and made into a 6.69 mol / L ammonia water solution (molar ratio of ammonia water:total metal salts = 1:2) to obtain the second precipitant ammonia water solution C.
[0055] Under the condition of 30 °C, the mixed metal salt solution A and the first precipitant mixed alkali solution B were simultaneously added dropwise into a 2 L three-necked flask containing the second precipitant ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the whole dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 12.5. After the dropping was completed, the temperature was raised to 60 °C and kept at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h, and finally 124.98 g of the iron-manganese binary composite precursor was obtained. Analyzed by a carbon-sulfur analyzer and ICP, the S content of its precursor was 0.029%, the Na content was 226.7 ppm, and the specific surface area was 189.2 m 2 / g; the Fe content was 26.48%, the Mn content was 39.13%. After calculation, its molar ratio of Mn / Fe was 0.600:0.400, the Fe yield was 98.5%, and the Mn yield was 98.9%.
[0056] The obtained iron-manganese binary composite precursor was observed by scanning electron microscopy, and the results were as Figure 1 . From Figure 1 it can be seen that the prepared iron-manganese binary composite precursor was aggregated by primary spherical particles, and the size of the primary particles was relatively uniform, about 100 nm in size. At the same time, the obtained iron-manganese binary composite precursor was characterized by XRD, and the results were as Figure 2 . From Figure 2 it can be known that the XRD pattern of the prepared iron-manganese binary composite precursor was in good agreement with the standard patterns of MnCO₃ (PDF card number 86-0172) and Mn₃O₄ (PDF card number 80-0382), which indicated that the prepared iron-manganese binary composite precursor was a mixture of manganese carbonate crystal phase and manganese tetroxide crystal phase, and the iron and manganese elements in the precursor existed in the manganese carbonate crystal phase and manganese tetroxide crystal phase in the form of coprecipitation. After analysis, the manganese tetroxide crystal phase in this precursor accounted for 65.77%, and the manganese carbonate crystal phase accounted for 26.48%.
[0057] Lithium iron manganese phosphate / carbon composite material:
[0058] The raw materials are fed according to the molar ratio of Li:(Fe+Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 56.03 g of lithium carbonate (99.5%), 170.39 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide are successively added to a 2 L measuring cup containing 800 mL of pure water, placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 350 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C and held at a constant temperature for 4 hours. After the tube furnace naturally cools to 80 °C, the sintered material is crushed to obtain 215.9 g of the prelithiated lithium iron manganese phosphate precursor.
[0059] 200.00 g of the prelithiated lithium iron manganese phosphate precursor, 16.00 g of glucose, and 16.00 g of polyethylene glycol 20000 are successively added to a 2 L measuring cup containing 800 mL of pure water, placed in a basket mill and ground at a speed of 2000 r / min for 40 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 300 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C and held at a constant temperature for 4 hours. After the tube furnace naturally cools to 80 °C, the sintered material is classified and crushed to finally obtain the LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0060] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet is made. Using metallic lithium as the negative electrode, a button cell is assembled. At 2-4.3 V and 25 °C, different charge-discharge current conditions are used for testing. The discharge curve results are shown in Figure 3 , the initial reversible capacity during charge-discharge at 0.1C is 155.2 mAh / g, the initial reversible capacity during charge-discharge at 0.2C is 152.7 mAh / g, and the initial reversible capacity during charge-discharge at 1C is 146.5 mAh / g.
[0061] Example 2
[0062] Preparation of the iron-manganese binary composite precursor:
[0063] Dissolve 114.24 g of iron(III) sulfate hydrate (Fe content 22%) and 177.45 g of manganese(II) sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 135.93 g of NaOH (96%) (molar ratio OH - : total metal salts = 2.18) and 111.30 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salts = 0.7:1) in 750 mL of deionized water to obtain a first precipitating agent mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salts = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0064] Under the condition of 30 °C, simultaneously drip the mixed metal salt solution A and the first precipitating agent mixed alkali solution B into a 2 L three-necked flask containing the second precipitating agent ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the whole dripping process, the stirring speed is 350 rpm / min, and the pH of the reaction system is 12.7. After the dripping is completed, heat up to 60 °C and keep the temperature constant for 4 h. During the reaction process, the stirring speed is 550 rpm / min. After the reaction is completed, filter, wash and suction-filter the product until the conductivity of the filtrate < 300 μS / cm; place the filtered cake in a blast drying oven at 100 °C for 12 h to finally obtain 123.57 g of an iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the S content of this precursor is 0.073%, the Na content is 233.9 ppm, and the specific surface area is 135.0 m 2 / g; the Fe content is 19.80%, the Mn content is 45.49%. After calculation, its molar ratio of Mn / Fe is 0.709:0.300, the Fe yield is 97.3%, and the Mn yield is 97.4%.
[0065] Lithium iron manganese phosphate / carbon composite material:
[0066] The raw materials are fed in according to the molar ratio of Li:(Fe+Mn):P = 1.05:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 55.33 g of lithium carbonate (99.5%), 169.80 g of ammonium dihydrogen phosphate (99%), 1.00 g of magnesium hydroxide, and 0.50 g of titanium dioxide are successively added to a 2 L measuring cup containing 800 mL of pure water, placed in a basket mill, and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 300 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 650 °C for 4 hours. After the tube furnace naturally cools down to 80 °C, the sintered material is crushed to obtain 206.7 g of the prelithiated lithium iron manganese phosphate precursor.
[0067] 200.00 g of the prelithiated lithium iron manganese phosphate precursor, 16.00 g of sucrose, and 4.00 g of starch are successively added to a 2 L measuring cup containing 800 mL of pure water, placed in a basket mill, and ground at a speed of 2000 r / min for 40 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 320 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 8 hours. After the tube furnace naturally cools down to 80 °C, the sintered material is classified and crushed to finally obtain the LiFe 0.3 Mn 0.7 PO4 / C composite material with a carbon content of 1.4%.
[0068] Using the prepared LiFe 0.3 Mn 0.7 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet is made. Using metallic lithium as the negative electrode, a button battery is assembled. At 2-4.3 V and 25 °C, different charge-discharge current conditions are used for testing. The initial reversible capacity during charge-discharge at 0.1C is 154.5 mAh / g, the initial reversible capacity during charge-discharge at 0.2C is 152.1 mAh / g, and the initial reversible capacity during charge-discharge at 1C is 144.7 mAh / g.
[0069] Example 3
[0070] Preparation of the iron-manganese binary composite precursor:
[0071] Dissolve 76.39 g of ferric sulfate hydrate (Fe content 22%) and 202.81 g of manganese sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 134.37 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.15) and 127.20 g of Na2CO3 (99%) (molar ratio CO3 2- : metal salt = 0.8:1) in 750 mL of deionized water to obtain a first precipitating agent mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water and prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salt = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0072] Under the condition of 30 °C, simultaneously drip the mixed metal salt solution A and the first precipitating agent mixed alkali solution B into a 2 L three-necked flask containing the second precipitating agent ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the whole dripping process, the stirring speed is 350 rpm / min, and the pH of the reaction system is 12.8. After the dripping is completed, raise the temperature to 60 °C and keep it reacting at a constant temperature for 4 h. During the reaction process, the stirring speed is 550 rpm / min. After the reaction is completed, filter, wash and suction-filter the product until the conductivity of the filtrate < 300 μS / cm; place the filtered cake in a blast drying oven at 100 °C and dry it for 12 h to finally obtain 121.90 g of a binary iron-manganese composite precursor. Through carbon-sulfur analyzer and ICP detection and analysis, for this precursor, its S content is 0.045%, Na content is 217.1 ppm, and the specific surface area is 102.3 m 2 / g; Fe content is 13.40%, Mn content is 52.90%. After calculation, its molar ratio of Mn / Fe is 0.801:0.199, Fe yield is 97.2%, and Mn yield is 97.9%.
[0073] Lithium iron manganese phosphate / carbon composite material:
[0074] The raw materials are fed in a molar ratio of Li:(Fe+Mn):P = 1.05:1:1.02. Successively, 120.00 g of the iron-manganese binary composite precursor, 56.28 g of lithium carbonate (99.5%), 171.10 g of ammonium dihydrogen phosphate (99%), 1.20 g of niobium pentoxide, and 0.50 g of magnesium oxide are added to a 2-L measuring cup containing 800 mL of pure water, placed in a planetary ball mill, and milled at a rotation speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 300 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 630 °C for 5 h. After the tube furnace naturally cools to 80 °C, the sintered material is crushed to obtain 218.7 g of the prelithiated lithium iron manganese phosphate precursor.
[0075] Successively, 200.00 g of the prelithiated lithium iron manganese phosphate precursor, 12.00 g of cyclodextrin, and 4.60 g of starch are added to a 2-L measuring cup containing 800 mL of pure water, placed in a planetary ball mill, and milled at a rotation speed of 2000 r / min for 35 min, and then milled at a rotation speed of 40 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 320 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 690 °C for 10 h. After the tube furnace naturally cools to 80 °C, the sintered material is classified and crushed to finally obtain the LiFe 0.2 Mn 0.8 PO4 / C composite material with a carbon content of 1.4%.
[0076] Using the prepared LiFe 0.2 Mn 0.8 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet is made. Using metallic lithium as the negative electrode, a button cell is assembled. At 2-4.3 V and 25 °C, different charge-discharge current conditions are used for testing. The initial reversible capacity for charge-discharge at 0.1C is 154.0 mAh / g, the initial reversible capacity for charge-discharge at 0.2C is 151.3 mAh / g, and the initial reversible capacity for charge-discharge at 1C is 143.8 mAh / g.
[0077] Example 4
[0078] Preparation of the iron-manganese binary composite precursor:
[0079] Dissolve 190.91 g of iron(III) sulfate hydrate (Fe content 22%) and 126.76 g of manganese(II) sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 149.99 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.4:1) and 79.50 g of Na2CO3 (99%) (molar ratio CO3 2- : metal salt = 0.5:1) in 750 mL of deionized water to obtain a first precipitating agent mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water and prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salt = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0080] At 30 °C, simultaneously drip the mixed metal salt solution A and the first precipitating agent mixed alkali solution B into a 2 L three-necked flask containing the second precipitating agent ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the entire dripping process, the stirring speed is 350 rpm / min, and the pH of the reaction system is 12.7. After the dripping is completed, raise the temperature to 60 °C and keep it at a constant temperature for 4 h. During the reaction process, the stirring speed is 550 rpm / min. After the reaction is completed, filter, wash, and suction-filter the product until the conductivity of the filtrate < 300 μS / cm; place the filtered cake in a blast drying oven at 100 °C and dry for 12 h to finally obtain 124.98 g of an iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the precursor has an S content of 0.022%, a Na content of 135.8 ppm, and a specific surface area of 238.2 m 2 / g; the Fe content is 32.75%, the Mn content is 32.18%. After calculation, its molar ratio of Mn / Fe is 0.500:0.500, the Fe yield is 98.8%, and the Mn yield is 99.0%.
[0081] Lithium iron manganese phosphate / carbon composite material:
[0082] The raw materials are fed in according to the molar ratio of Li:(Fe+Mn):P = 1.05:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 54.84 g of lithium carbonate (99.5%), 168.35 g of ammonium dihydrogen phosphate (99%), 1.12 g of nickel acetate, and 0.62 g of magnesium oxide are successively added to a 2 L measuring cup containing 800 mL of ethanol, and placed in a planetary ball mill to grind at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 350 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C for 6 hours. After the tube furnace naturally cools to 80 °C, the sintered material is crushed to obtain 215.6 g of the prelithiated lithium iron manganese phosphate precursor.
[0083] 200.00 g of the prelithiated lithium iron manganese phosphate precursor, 15.6 g of glucose, and 2.1 g of fructose are successively added to a 2 L measuring cup containing 800 mL of ethanol, and placed in a planetary ball mill to grind at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1-2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 350 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 8 hours. After the tube furnace naturally cools to 80 °C, the sintered material is classified and crushed to finally obtain the LiFe 0.5 Mn 0.5 PO4 / C composite material with a carbon content of 1.62%.
[0084] Using the prepared LiFe 0.5 Mn 0.5 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet is made. Using metallic lithium as the negative electrode, a coin cell is assembled. At 25 °C under the conditions of 2-4.3 V, different charge-discharge current conditions are tested. The initial reversible capacity for charge-discharge at 0.1C is 156.1 mAh / g, the initial reversible capacity for charge-discharge at 0.2C is 153.4 mAh / g, and the initial reversible capacity for charge-discharge at 1C is 146.9 mAh / g.
[0085] Example 5
[0086] Preparation of the iron-manganese binary composite precursor:
[0087] Dissolve 242.39 g of ferric nitrate nonahydrate (purity 99.9%) and 322.06 g of 50% manganese nitrate solution in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 149.99 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.4) and 95.40 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salt = 0.6:1) in 750 mL of deionized water to obtain a first precipitant mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salt = 1:2) to obtain a second precipitant ammonia water solution C.
[0088] Under the condition of 30 °C, simultaneously drip the mixed metal salt solution A and the first precipitant mixed alkali solution B into a 2 L three-necked flask containing the second precipitant ammonia water solution C through a peristaltic pump at a rate of 12.5 mL / min for 60 min. During the whole dripping process, the stirring speed is 350 rpm / min, and the pH of the reaction system is 12.9. After the dripping is completed, heat up to 50 °C and keep the temperature constant for 6 h. During the reaction process, the stirring speed is 550 rpm / min. After the reaction is completed, filter, wash and suction-filter the product until the conductivity of the filtrate < 300 μS / cm; place the filtered cake in a blast drying oven at 100 °C for 12 h to finally obtain 124.50 g of the iron-manganese binary composite precursor. Through carbon-sulfur analyzer and ICP detection and analysis, the Na content of this precursor is 184.6 ppm, and the specific surface area is 199.4 m 2 / g; the Fe content is 25.92%, the Mn content is 38.54%. After calculation, its molar ratio of Mn / Fe is 0.602:0.398, the Fe yield is 96.0%, and the Mn yield is 97.0%.
[0089] Lithium iron manganese phosphate / carbon composite material:
[0090] The raw materials are fed according to the molar ratio of Li:(Fe + Mn):P = 1.03:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 151.24 g of lithium dihydrogen phosphate (99%), 0.85 g of magnesium hydroxide, and 0.61 g of zirconium dioxide are successively added to a 2 L measuring cup containing 800 mL of ethanol, and placed in a planetary ball mill to grind at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1 - 2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 380 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C for 6 hours. After the tube furnace naturally cools to 80 °C, the sintered material is crushed to obtain 213.2 g of the prelithiated lithium iron manganese phosphate precursor.
[0091] 200.00 g of the prelithiated lithium iron manganese phosphate precursor, 16.0 g of glucose, and 4.0 g of cellulose are successively added to a 2 L measuring cup containing 800 mL of ethanol, and placed in a planetary ball mill to grind at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1 - 2 μm, the slurry is introduced into a sand mill for fine grinding. After the particle size of the slurry reaches 320 nm, the slurry is spray-dried. After the spray drying is completed, the dried and crushed material is placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 8 hours. After the tube furnace naturally cools to 80 °C, the sintered material is classified and crushed to finally obtain the LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0092] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the cathode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet is made. Using metallic lithium as the anode, a coin cell is assembled. At 2 - 4.3 V and 25 °C, different charge-discharge current conditions are used for testing. The initial reversible capacity for charge-discharge at 0.1 C is 155.1 mAh / g, the initial reversible capacity for charge-discharge at 0.2 C is 152.8 mAh / g, and the initial reversible capacity for charge-discharge at 1 C is 145.6 mAh / g.
[0093] Example 6
[0094] Preparation of the iron-manganese binary composite precursor:
[0095] 97.32 g of anhydrous ferric chloride (purity 99%) and 178.11 g of manganese chloride tetrahydrate (purity 99%) are dissolved in 750 mL of deionized water to obtain a mixed metal salt solution A. Then 131.24 g of NaOH (96%) (molar ratio OH- : Total metal salts = 2.1), 127.20 g of Na2CO3 (99%) (molar ratio of CO3 2- : Total metal salts = 0.8:1) was dissolved in 750 mL of deionized water to obtain the first precipitant mixed alkali solution B. 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water were weighed and made into a 6.69 mol / L ammonia water solution (molar ratio of ammonia water: total metal salts = 1:2) to obtain the second precipitant ammonia water solution C.
[0096] At 30 °C, the mixed metal salt solution A and the first precipitant mixed alkali solution B were simultaneously added dropwise to a 2 L three-necked flask containing the second precipitant ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the whole dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 12.3. After the dropping was completed, the temperature was raised to 70 °C and kept at a constant temperature for 2 h. During the reaction process, the stirring speed was 650 rpm / min. After the reaction was completed, the product was filtered, washed, and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h to finally obtain 124.98 g of the iron-manganese binary composite precursor. After detection and analysis, the Na content was 176.1 ppm, and the specific surface area was 182.9 m 2 / g; the Fe content was 25.99%, the Mn content was 38.50%. After calculation, the molar ratio of Mn / Fe was 0.601:0.399, the Fe yield was 96.7%, and the Mn yield was 97.7%.
[0097] Lithium iron manganese phosphate / carbon composite material:
[0098] The raw materials were fed according to the molar ratio of Li:(Fe + Mn):P = 1.08:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 56.12 g of lithium carbonate (99.5%), 167.49 g of ammonium dihydrogen phosphate (99%), and 1.5 g of magnesium hydroxide were successively added to a 2 L measuring cup containing 800 mL of pure water and placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 400 nm, the slurry was spray dried. After the spray drying was completed, the dried and crushed material was placed in a tubular furnace under a nitrogen atmosphere and sintered at a sintering temperature of 500 °C for 5 h. After the tubular furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 213.3 g of the prelithiated lithium iron manganese phosphate precursor.
[0099] Add 200.00 g of prelithiated lithium iron manganese phosphate precursor, 15.00 g of cyclodextrin, and 4.00 g of starch into a 2 L measuring cup containing 800 mL of pure water in sequence, place it in a basket mill and grind at a speed of 2000 r / min for 30 min. After the particle size of the slurry reaches 1 - 2 μm, transfer the slurry to a sand mill for fine grinding. After the particle size of the slurry reaches 320 nm, spray-dry this slurry. After the spray drying is completed, place the dried and crushed material in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 720 °C and keep it at a constant temperature for 10 hours. After the tube furnace naturally cools down to 80 °C, perform classification crushing on the sintered material to finally obtain LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0100] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the cathode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder to make an electrode sheet. Using metallic lithium as the anode, assemble it into a button cell. At 2 - 4.3 V and 25 °C, test under different charge-discharge current conditions. The initial reversible capacity for charge-discharge at 0.1 C is 154.8 mAh / g, the initial reversible capacity for charge-discharge at 0.2 C is 152.1 mAh / g, and the initial reversible capacity for charge-discharge at 1 C is 144.9 mAh / g.
[0101] Example 7
[0102] Preparation of iron-manganese binary composite precursor:
[0103] Dissolve 152.73 g of ferric sulfate hydrate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) into 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 156.24 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.5) into 250 mL of deionized water, and dissolve 71.16 g of NH4HCO3 (99%) (molar ratio HCO3 - : total metal salt = 0.6:1) into 500 mL of deionized water. After cooling to room temperature, mix the above two alkali solutions to obtain a first precipitating agent mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salt = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0104] At 30 °C, the mixed metal salt solution A and the first precipitant mixed alkali solution B were simultaneously added dropwise into a 2 L three-necked flask containing the second precipitant ammonia water solution C through a peristaltic pump at 50 mL / min for 15 min. During the whole dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 12.9. After the dropping was completed, the temperature was raised to 70 °C and kept at a constant temperature for 6 h. During the reaction process, the stirring speed was 450 rpm / min. After the reaction was completed, the product was filtered, washed and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C for 12 h, and finally 124.35 g of the iron-manganese binary composite precursor was obtained. Analyzed by a carbon-sulfur analyzer and ICP, the S content of the precursor was 0.030%, the Na content was 191.3 ppm, and the specific surface area was 157.7 m 2 / g; the Fe content was 26.01%, the Mn content was 38.24%. After calculation, the molar ratio of Mn / Fe was 0.599:0.401, the Fe yield was 96.2%, and the Mn yield was 96.2%.
[0105] Lithium iron manganese phosphate / carbon composite material:
[0106] The raw materials were fed according to the molar ratio of Li:(Fe + Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 54.87 g of lithium carbonate (99.5%), 166.86 g of ammonium dihydrogen phosphate (99%), 1.20 g of niobium pentoxide, and 0.60 titanium dioxide were successively added to a 2 L measuring cup containing 800 mL of pure water and placed in a basket mill for grinding at 2000 r / min for 30 min. After the particle size of the slurry reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 450 nm, the slurry was spray dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 210.9 g of the prelithiated lithium iron manganese phosphate precursor.
[0107] Add 200.00 g of prelithiated lithium iron manganese phosphate precursor, 16.00 g of rock sugar, and 8.00 g of polyethylene glycol 20000 to a 2 L measuring cup containing 800 mL of pure water. Place it in a basket mill and grind at a speed of 2000 r / min for 30 min. After the slurry particle size reaches 1 - 2 μm, transfer the slurry to a sand mill for fine grinding. After the slurry particle size reaches 320 nm, spray-dry this slurry. After the spray drying is completed, place the dried and crushed material in a tubular furnace under a nitrogen atmosphere for sintering at a sintering temperature of 720 °C for 10 hours. After the tubular furnace naturally cools to 80 °C, perform fractional crushing on the sintered material to finally obtain a LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0108] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, make an electrode sheet. Using metallic lithium as the negative electrode, assemble it into a coin cell. At 2 - 4.3 V and 25 °C, test under different charge-discharge current conditions. The initial reversible capacity for charge-discharge at 0.1 C is 154.5 mAh / g, the initial reversible capacity for charge-discharge at 0.2 C is 152.3 mAh / g, and the initial reversible capacity for charge-discharge at 1 C is 144.5 mAh / g.
[0109] Comparative Example 1
[0110] Compared with Example 1, the difference is that sodium carbonate is not added.
[0111] Preparation of iron-manganese binary composite precursor:
[0112] Dissolve 152.73 g of ferric sulfate hydrate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 137.49 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.2) in 750 mL of deionized water to obtain the first precipitating agent alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salt = 1:2) to obtain the second precipitating agent ammonia water solution C.
[0113] At 30 °C, the mixed metal salt solution A and the first precipitant alkali solution B were simultaneously added dropwise to a 2 L three-necked flask containing the second precipitant ammonia solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the entire dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 11.7. After the dropping was completed, the temperature was raised to 60 °C and the reaction was carried out at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed, and suction-filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h to finally obtain 123.27 g of the iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the S content of the precursor was 0.605%, the Na content was 4175.8 ppm, and the specific surface area was 212.3 m 2 / g; the Fe content was 25.17%, the Mn content was 37.53%. After calculation, the molar ratio of Mn / Fe was 0.603:0.397, the Fe yield was 92.4%, and the Mn yield was 93.6%.
[0114] Lithium iron manganese phosphate / carbon composite material:
[0115] The raw materials were fed according to the molar ratio of Li:(Fe + Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 53.56 g of lithium carbonate (99.5%), 162.84 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide were successively added to a 2 L measuring cup containing 800 mL of pure water, and ground in a basket mill at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 350 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C and held at a constant temperature for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 207.1 g of the prelithiated lithium iron manganese phosphate precursor.
[0116] Add 200.00 g of pre-lithiated lithium iron manganese phosphate precursor, 16.00 g of glucose, and 16.00 g of polyethylene glycol 20000 to a 2 L measuring cup containing 800 mL of pure water, place it in a planetary ball mill, and grind it at a speed of 2000 r / min for 40 min. After the particle size of the slurry reaches 1 - 2 μm, transfer the slurry to a sand mill for fine grinding. After the particle size of the slurry reaches 300 nm, spray-dry this slurry. After spray-drying is completed, place the dried and crushed material in a tubular furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 hours. After the tubular furnace naturally cools to 80 °C, crush the sintered material by classification, and finally obtain a LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0117] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, make an electrode sheet, use metallic lithium as the negative electrode, and assemble it into a coin cell. At 2 - 4.3 V and 25 °C, test it under different charge-discharge current conditions. The initial reversible capacity during charge-discharge at 0.1 C is 152.1 mAh / g, the initial reversible capacity during charge-discharge at 0.2 C is 149.8 mAh / g, and the initial reversible capacity during charge-discharge at 1 C is 140.5 mAh / g.
[0118] Comparative Example 2
[0119] Compared with Example 1, the difference is that sodium hydroxide is not added, and the addition amount of sodium carbonate is 190.8 g (molar ratio CO3 2- : total metal salts = 1.2:1).
[0120] Preparation of iron-manganese binary composite precursor:
[0121] Dissolve 152.73 g of hydrated ferric sulfate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 190.80 g of Na2CO3 (99%) (molar ratio CO3 - : total metal salts = 1.2:1) in 750 mL of deionized water to obtain a first precipitating agent alkaline solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: metal salts = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0122] At 30 °C, the mixed metal salt solution A and the first precipitating agent alkali solution B were simultaneously added dropwise to a 2 L three-necked flask containing the second precipitating agent ammonia water solution C through a peristaltic pump at 25 mL / min for 30 min. During the entire dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 7.5. After the dropping was completed, the temperature was raised to 60 °C and the reaction was carried out at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed, and suction-filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h to finally obtain 133.61 g of the iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the precursor had an S content of 0.009%, a Na content of 5491.3 ppm, and a specific surface area of 148.9 m 2 / g; the Fe content was 22.03%, the Mn content was 32.41%. After calculation, the molar ratio of Mn / Fe was 0.599:0.401, the Fe yield was 87.8%, and the Mn yield was 87.56%.
[0123] Lithium iron manganese phosphate / carbon composite material:
[0124] The raw materials were fed in a molar ratio of Li:(Fe + Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 46.49 g of lithium carbonate (99.5%), 141.39 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide were successively added to a 2 L measuring cup containing 800 mL of pure water, placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1-2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 350 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C and held at a constant temperature for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 180.51 g of the prelithiated lithium iron manganese phosphate precursor.
[0125] 180.00 g of pre-lithiated lithium iron manganese phosphate precursor, 14.80 g of glucose, and 14.50 g of polyethylene glycol 20000 were successively added to a 2 L measuring cup containing 800 mL of pure water, and placed in a basket mill for grinding at a speed of 2000 r / min for 40 min. After the slurry particle size reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the slurry particle size reached 300 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 hours. After the tube furnace naturally cooled to 80 °C, the sintered material was classified and crushed, and finally a LiFe 0.4 Mn 0.6 PO4 / C composite material was obtained.
[0126] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet was made. Using metallic lithium as the negative electrode, a button cell was assembled. At 2 - 4.3 V and 25 °C, different charge and discharge current conditions were tested. The initial reversible capacity at 0.1 C charge and discharge was 151.0 mAh / g, the initial reversible capacity at 0.2 C charge and discharge was 149.5 mAh / g, and the initial reversible capacity at 1 C charge and discharge was 140.1 mAh / g.
[0127] Comparative Example 3
[0128] Compared with Example 1, the difference is that ammonia water is not used.
[0129] Preparation of iron-manganese binary composite precursor:
[0130] 152.73 g of hydrated ferric sulfate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) were dissolved in 750 mL of deionized water to obtain a mixed metal salt solution A. Then, 137.49 g of NaOH (96%) (molar ratio OH - : total metal salt = 2.2) was dissolved in 250 mL of deionized water to obtain a first precipitating agent alkali solution B. Then, 95.40 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salt = 0.6:1) was dissolved in 500 mL of deionized water to obtain a second precipitating agent alkali solution C.
[0131] At 30 °C, the mixed metal salt solution A and the second precipitant alkali solution C were simultaneously added dropwise into a 2 L three-necked flask containing the first precipitant alkali solution B through peristaltic pumps at 25 mL / min and 16.7 mL / min respectively. The dropping time was 30 min. During the whole dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 12.5. After the dropping was completed, the temperature was raised to 60 °C and the reaction was carried out at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h, and finally 126.02 g of the iron-manganese binary composite precursor was obtained. Through the detection and analysis of a carbon-sulfur analyzer and ICP, the S content of this precursor was 0.085%, the Na content was 385.9 ppm, and the specific surface area was 166.1 m 2 / g; the Fe content was 25.31%, the Mn content was 36.96%. After calculation, the molar ratio of Mn / Fe was 0.598:0.402, the Fe recovery rate was 94.9%, and the Mn recovery rate was 94.2%.
[0132] Lithium iron manganese phosphate / carbon composite material:
[0133] The raw materials were fed according to the molar ratio of Li:(Fe + Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 53.2 g of lithium carbonate (99.5%), 161.7 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide were successively added into a 2 L measuring cup containing 800 mL of pure water, and placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1-2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 350 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tubular furnace under a nitrogen atmosphere for sintering. The sintering temperature was 600 °C and the constant temperature was 4 hours. After the tubular furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 207.93 g of the prelithiated lithium iron manganese phosphate precursor.
[0134] 200.00 g of the prelithiated lithium iron manganese phosphate precursor, 16.00 g of glucose, and 16.00 g of polyethylene glycol 20000 were successively added to a 2 L measuring cup containing 800 mL of pure water, and the mixture was placed in a planetary ball mill and milled at a speed of 2000 r / min for 40 min. After the particle size of the slurry reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 300 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was classified and crushed, and finally, a LiFe 0.4 Mn 0.6 PO4 / C composite material was obtained.
[0135] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the cathode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet was made. Using metallic lithium as the anode, a button cell was assembled. At 2 - 4.3 V and 25 °C, different charge-discharge current conditions were used for testing. The initial reversible capacity during charge-discharge at 0.1C was 150.9 mAh / g, the initial reversible capacity during charge-discharge at 0.2C was 149.5 mAh / g, and the initial reversible capacity during charge-discharge at 1C was 138.6 mAh / g.
[0136] Comparative Example 4
[0137] Compared with Example 1, the difference lies in that the addition amount of sodium hydroxide is 162.49 g (molar ratio OH - : total metal salts = 2.6). Preparation of the iron-manganese binary composite precursor:
[0138] 152.73 g of hydrated ferric sulfate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) were dissolved in 750 mL of deionized water to obtain a mixed metal salt solution A. Then, 162.49 g of NaOH (96%) (molar ratio OH - : total metal salts = 2.6) and 95.40 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salts = 0.6:1) were dissolved in 750 mL of deionized water to obtain a first precipitating agent mixed alkali solution B. 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water were weighed and made into a 6.69 mol / L ammonia water solution (molar ratio ammonia water:total metal salts = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0139] At 30 °C, the mixed metal salt solution A and the first precipitant mixed alkali solution B were simultaneously added dropwise into a 2 L three-necked flask containing the second precipitant ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the whole dropping process, the stirring speed was 350 rpm / min and the pH of the reaction system was 13.3. After the dropping was completed, the temperature was raised to 60 °C and the reaction was carried out at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h to finally obtain 123.64 g of the iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the S content of its precursor was 0.298%, the Na content was 3557.7 ppm, and the specific surface area was 190.7 m 2 / g; the Fe content was 25.04%, the Mn content was 37.88%. After calculation, the molar ratio of Mn / Fe was 0.606:0.394, the Fe yield was 92.1%, and the Mn yield was 94.7%.
[0140] Lithium iron manganese phosphate / carbon composite material:
[0141] The raw materials were fed according to the molar ratio of Li:(Fe + Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 53.74 g of lithium carbonate (99.5%), 163.42 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide were successively added to a 2 L measuring cup containing 800 mL of pure water, and placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 350 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C and held at a constant temperature for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 210.73 g of the prelithiated lithium iron manganese phosphate precursor.
[0142] Add 200.00 g of prelithiated lithium iron manganese phosphate precursor, 16.00 g of glucose, and 16.00 g of polyethylene glycol 20000 to a 2 L measuring cup containing 800 mL of pure water, place it in a basket mill, and grind it at a speed of 2000 r / min for 40 min. After the particle size of the slurry reaches 1 - 2 um, transfer the slurry to a sand mill for fine grinding. After the particle size of the slurry reaches 300 nm, spray-dry this slurry. After the spray drying is completed, place the dried and crushed material in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 hours. After the tube furnace naturally cools to 80 °C, perform classification crushing on the sintered material, and finally obtain a LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0143] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, make an electrode sheet, use metallic lithium as the negative electrode, and assemble it into a button cell. At 2 - 4.3 V and 25 °C, test under different charge-discharge current conditions. The initial reversible capacity for charge-discharge at 0.1 C is 150.1 mAh / g, the initial reversible capacity for charge-discharge at 0.2 C is 149.5 mAh / g, and the initial reversible capacity for charge-discharge at 1 C is 138.3 mAh / g.
[0144] Comparative Example 5
[0145] Compared with Example 1, the difference is that the addition amount of sodium hydroxide is 112.49 g (molar ratio NaOH: metal salt = 1.8). Preparation of the iron-manganese binary composite precursor:
[0146] Dissolve 152.73 g of ferrous sulfate heptahydrate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 112.49 g of NaOH (96%) (molar ratio OH - : total metal salt = 1.8), 95.40 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salt = 0.6:1) in 750 mL of deionized water to obtain a first precipitating agent mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salt = 1:2), and obtain a second precipitating agent ammonia water solution C.
[0147] At 30 °C, the mixed metal salt solution A and the first precipitant mixed alkali solution B were simultaneously added dropwise into a 2 L three-necked flask containing the second precipitant ammonia water solution C through a peristaltic pump at 25 mL / min for 30 min. During the whole dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 10.6. After the dropping was completed, the temperature was raised to 60 °C and kept at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C for 12 h, and finally 136.42 g of the iron-manganese binary composite precursor was obtained. Analyzed by a carbon-sulfur analyzer and ICP, the S content of the precursor was 0.359%, the Na content was 4254.3 ppm, and the specific surface area was 180.1 m 2 / g; the Fe content was 22.34%, the Mn content was 33.60%. After calculation, the molar ratio of Mn / Fe was 0.605:0.395, the Fe yield was 90.2%, and the Mn yield was 92.7%.
[0148] Lithium iron manganese phosphate / carbon composite material:
[0149] The raw materials were fed according to the molar ratio of Li:(Fe+Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 47.78 g of lithium carbonate (99.5%), 145.29 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide were successively added into a 2 L measuring cup containing 800 mL of pure water, and placed in a basket mill for grinding at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1-2 um, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 350 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 185.83 g of the prelithiated lithium iron manganese phosphate precursor.
[0150] Add 180.00 g of pre-lithiated lithium iron manganese phosphate precursor, 15.00 g of glucose, and 15.00 g of polyethylene glycol 20000 to a 2 L measuring cup containing 800 mL of pure water, place it in a basket mill, and grind it at a speed of 2000 r / min for 40 min. After the slurry particle size reaches 1 - 2 μm, transfer the slurry to a sand mill for fine grinding. After the slurry particle size reaches 300 nm, spray-dry this slurry. After the spray drying is completed, place the dried and crushed material in a tubular furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 hours. After the tubular furnace naturally cools to 80 °C, crush the sintered material by grading to finally obtain a LiFe 0.4 Mn 0.6 PO4 / C composite material.
[0151] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder to make an electrode sheet. Using metallic lithium as the negative electrode, assemble it into a button cell. At 2 - 4.3 V and 25 °C, test it under different charge and discharge current conditions. The initial reversible capacity during charge and discharge at 0.1C is 151.9 mAh / g, the initial reversible capacity during charge and discharge at 0.2C is 149.8 mAh / g, and the initial reversible capacity during charge and discharge at 1C is 138.5 mAh / g.
[0152] Comparative Example 6
[0153] Compared with Example 1, the difference is that the amount of sodium carbonate used is 15.90 g (molar ratio CO3 2- : total metal salts = 0.1:1). Preparation of the iron-manganese binary composite precursor:
[0154] Dissolve 152.73 g of hydrated ferric sulfate (Fe content 22%) and 152.10 g of manganese sulfate monohydrate (purity 99.9%) in 750 mL of deionized water to obtain a mixed metal salt solution A. Then dissolve 137.49 g of NaOH (96%) (molar ratio OH - : total metal salts = 2.2), 15.90 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salts = 0.1:1) in 750 mL of deionized water to obtain the first precipitant mixed alkali solution B. Weigh 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water to prepare a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salts = 1:2) to obtain the second precipitant ammonia water solution C.
[0155] At 30 °C, the mixed metal salt solution A and the first precipitating agent mixed alkali solution B were simultaneously added dropwise into a 2 L three-necked flask containing the second precipitating agent ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the entire dropping process, the stirring speed was 350 rpm / min and the pH of the reaction system was 12.2. After the dropping was completed, the temperature was raised to 60 °C and the reaction was carried out at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed and suction filtered until the conductivity of the filtrate < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h to finally obtain 124.05 g of the iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the S content of this precursor was 0.239%, the Na content was 4496.3 ppm, and the specific surface area was 185.4 m 2 / g; the Fe content was 25.72%, the Mn content was 38.04%. After calculation, the molar ratio of Mn / Fe was 0.601:0.399, the Fe yield was 94.9%, and the Mn yield was 95.4%.
[0156] Lithium iron manganese phosphate / carbon composite material:
[0157] The raw materials were fed according to the molar ratio of Li:(Fe + Mn):P = 1.06:1:1.03. 120.00 g of the iron-manganese binary composite precursor, 54.46 g of lithium carbonate (99.5%), 165.59 g of ammonium dihydrogen phosphate (99%), and 1.50 g of magnesium oxide were successively added into a 2 L measuring cup containing 800 mL of pure water, and placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1-2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 350 nm, the slurry was spray dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 600 °C for 4 h. After the tube furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 213.28 g of the prelithiated lithium iron manganese phosphate precursor.
[0158] 200.00 g of pre-lithiated lithium iron manganese phosphate precursor, 16.00 g of glucose, and 16.00 g of polyethylene glycol 20000 were successively added to a 2 L measuring cup containing 800 mL of pure water, and placed in a planetary ball mill for grinding at a speed of 2000 r / min for 40 min. After the slurry particle size reached 1 - 2 μm, the slurry was introduced into a sand mill for fine grinding. After the slurry particle size reached 300 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 700 °C for 4 hours. After the tube furnace naturally cooled to 80 °C, the sintered material was classified and crushed, and finally a LiFe 0.4 Mn 0.6 PO4 / C composite material was obtained.
[0159] Using the prepared LiFe 0.4 Mn 0.6 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, an electrode sheet was made. Using metallic lithium as the negative electrode, a coin cell was assembled. At 2 - 4.3 V and 25 °C, different charge-discharge current conditions were used for testing. The initial reversible capacity was 151.5 mAh / g at 0.1 C charge-discharge, 149.9 mAh / g at 0.2 C charge-discharge, and 137.5 mAh / g at 1 C charge-discharge.
[0160] Comparative Example 7
[0161] Compared with Example 3, the difference is that the amount of sodium carbonate used is 47.70 g (molar ratio CO3 2- : total metal salts = 0.3:1). Preparation of the iron-manganese binary composite precursor:
[0162] 76.36 g of hydrated ferric sulfate (Fe content 22%) and 202.81 g of manganese sulfate monohydrate (purity 99.9%) were dissolved in 750 mL of deionized water to obtain a mixed metal salt solution A. Then, 134.37 g of NaOH (96%) (molar ratio OH - : total metal salts = 2.15), 47.70 g of Na2CO3 (99%) (molar ratio CO3 2- : total metal salts = 0.3:1) were dissolved in 750 mL of deionized water to obtain a first precipitating agent mixed alkali solution B. 56.26 mL of concentrated ammonia water (NH3 content 25%) and 56.26 mL of pure water were weighed and prepared into a 6.69 mol / L ammonia water solution (molar ratio ammonia water: total metal salts = 1:2) to obtain a second precipitating agent ammonia water solution C.
[0163] At 30 °C, the mixed metal salt solution A and the first precipitating agent mixed alkali solution B were simultaneously added dropwise into a 2 L three-necked flask containing the second precipitating agent ammonia water solution C through a peristaltic pump at a rate of 25 mL / min for 30 min. During the entire dropping process, the stirring speed was 350 rpm / min, and the pH of the reaction system was 12.4. After the dropping was completed, the temperature was raised to 60 °C and kept at a constant temperature for 4 h. During the reaction process, the stirring speed was 550 rpm / min. After the reaction was completed, the product was filtered, washed, and suction-filtered until the conductivity of the filtrate was < 300 μS / cm; the filtered cake was placed in a blast drying oven at 100 °C and dried for 12 h to finally obtain 122.44 g of the iron-manganese binary composite precursor. Analyzed by a carbon-sulfur analyzer and ICP, the S content of this precursor was 0.365%, the Na content was 3297.2 ppm, and the specific surface area was 102.9 m 2 / g; the Fe content was 13.26%, the Mn content was 52.28%. After calculation, the molar ratio of Mn / Fe was 0.800:0.200, the Fe yield was 96.6%, and the Mn yield was 97.1%.
[0164] Lithium iron manganese phosphate / carbon composite material:
[0165] The raw materials were fed in according to the molar ratio of Li:(Fe + Mn):P = 1.05:1:1.02. 120.00 g of the iron-manganese binary composite precursor, 55.63 g of lithium carbonate (99.5%), 169.12 g of ammonium dihydrogen phosphate (99%), 1.20 g of niobium pentoxide, and 0.50 g of magnesium oxide were successively added into a 2 L measuring cup containing 800 mL of pure water, and placed in a basket mill and ground at a speed of 2000 r / min for 30 min. After the particle size of the slurry reached 1-2 μm, the slurry was introduced into a sand mill for fine grinding. After the particle size of the slurry reached 300 nm, the slurry was spray-dried. After the spray drying was completed, the dried and crushed material was placed in a tubular furnace under a nitrogen atmosphere for sintering at a sintering temperature of 630 °C and kept at a constant temperature for 5 h. After the tubular furnace naturally cooled to 80 °C, the sintered material was crushed to obtain 215.7 g of the prelithiated lithium iron manganese phosphate precursor.
[0166] Add 200.00 g of pre-lithiated lithium iron manganese phosphate precursor, 12.00 g of cyclodextrin, and 4.60 g of starch into a 2 L measuring cup containing 800 mL of pure water in sequence. Place it in a basket mill and grind at a speed of 2000 r / min for 35 min, and then grind at a speed of 40 min. After the particle size of the slurry reaches 1 - 2 μm, import the slurry into a sand mill for fine grinding. After the particle size of the slurry reaches 320 nm, spray-dry this slurry. After the spray drying is completed, place the dried and crushed material in a tube furnace under a nitrogen atmosphere for sintering at a sintering temperature of 690 °C for 10 hours. After the tube furnace naturally cools down to 80 °C, perform classification and crushing on the sintered material, and finally obtain a LiFe 0.2 Mn 0.8 PO4 / C composite material.
[0167] Using the prepared LiFe 0.2 Mn 0.8 PO4 / C composite material as the positive electrode material, acetylene black as the conductive agent, and polytetrafluoroethylene as the binder, make an electrode sheet, use metallic lithium as the negative electrode, and assemble it into a button cell. At 2 - 4.3 V and 25 °C, test under different charge-discharge current conditions. The initial reversible capacity for charge-discharge at 0.1 C is 151.0 mAh / g, the initial reversible capacity for charge-discharge at 0.2 C is 149.5 mAh / g, and the initial reversible capacity for charge-discharge at 1 C is 138.9 mAh / g.
[0168] The impurity content of Examples 1 - 7 of the present invention is low, the specific surface area is high, and the electrochemical performance is good, which is not easy to achieve simultaneously. Among them, the S content is 0.022 - 0.045%, and the Na content is 135.8 - 217.1 ppm; in Comparative Example 1, sodium carbonate is not added, in Comparative Examples 6 - 7, the addition amount of sodium carbonate is changed, in Comparative Example 2, sodium hydroxide is not added, and in Comparative Examples 4 - 5, the addition amount of sodium hydroxide is changed, all of which result in an increase in the impurity content and a decrease in the initial reversible capacity of charge-discharge.
[0169] In Comparative Example 3, ammonia water is not used, and the distribution uniformity of Fe / Mn elements in the product is poor, resulting in a decrease in the initial reversible capacity of charge-discharge.
[0170] The above detailed description is a specific description of one feasible embodiment of the present invention. This embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or change without departing from the present invention should be included within the scope of the technical solution of the present invention.
Claims
1. A preparation method of an iron-manganese binary composite precursor, characterized in that, It includes the following steps: simultaneously dropping an iron and manganese mixed metal salt solution and a mixed alkali solution into an ammonia water solution, performing a coprecipitation reaction after dropping, filtering, washing, and drying to obtain an iron-manganese binary composite precursor; The mixed alkali solution is a hydroxide and a carbonate or bicarbonate dissolved in water; The total concentration of the hydroxide and the carbonate or bicarbonate is 4.0 mol / L - 10.0 mol / L; the molar ratio of carbonate or bicarbonate to the total iron and manganese metal elements in the mixed alkali solution is (0.4 - 0.9):1; the molar ratio of the hydroxide to the total iron and manganese metal elements in the mixed alkali solution is (2.0 - 2.5):1; the concentration of the ammonia water solution is 5.35 - 13.38 mol / L, and the molar ratio of ammonia to the total iron and manganese elements is (0.5 - 1.5):1; the pH value of the coprecipitation reaction is 11.0 - 13.
0.
2. The preparation method according to claim 1, characterized in that, In the iron and manganese mixed metal salt, iron is a trivalent iron salt and manganese is a divalent manganese salt; the total metal concentration in the iron and manganese mixed metal salt solution is 0.5 mol / L - 5 mol / L, and the molar ratio of manganese to iron is x:(1 - x), where x is 0.5 - 0.9; the carbonate is at least one of ammonium carbonate, sodium carbonate, and potassium carbonate; the bicarbonate is at least one of ammonium bicarbonate and sodium bicarbonate; the hydroxide is at least one of potassium hydroxide, sodium hydroxide, and ammonia water.
3. The preparation method according to claim 1, characterized in that, The temperature of the coprecipitation reaction is 40°C - 70°C, and the time is 2 h - 8 h; for the simultaneous dropping, the dropping time is 15 min - 120 min; the dropping temperature is 20 - 30°C; for the washing, the conductivity of the filtrate after washing is lower than 300 μS / cm.
4. A method for preparing a lithium iron manganese phosphate / carbon composite material, characterized in that, It includes the following steps: S1. Mix and grind the iron-manganese binary composite precursor according to any one of claims 1 - 3 with a lithium salt, a phosphorus salt, and an additive in a liquid phase system, spray dry, and sinter in an inert atmosphere to obtain a prelithiated lithium iron manganese phosphate precursor; S2. Take the prelithiated lithium iron manganese phosphate precursor obtained in step S1 and a carbon source, grind and mix them in a liquid phase system, spray dry to obtain a lithium iron manganese phosphate / carbon composite precursor; S3. Sinter the lithium iron manganese phosphate / carbon composite precursor obtained in step S2 in an inert atmosphere to obtain a lithium iron manganese phosphate / carbon composite material.
5. The preparation method according to claim 4, characterized in that, In step S1, the lithium salt is at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; the phosphorus salt is at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, and lithium phosphate; the additive is at least one of titanium dioxide, tetrabutyl titanate, magnesium hydroxide, magnesium oxide, magnesium acetate, magnesium nitrate, zirconium dioxide, zirconium hydroxide, niobium pentoxide, nickel acetate, and nickel oxide; the addition amount of the additive is 0-1.0% of the mass of the prelithiated lithium iron manganese phosphate precursor; the molar ratio of the lithium salt, the iron-manganese binary composite precursor, and the phosphorus salt in step S1 is (1.1-1.0):1:(1.1-1.0); the sintering temperature in step S1 is 400-700 °C, and the time is 2-6 h; the inert atmosphere is any one of nitrogen, argon, and helium; the liquid phase system in steps S1 and S2 is any one of water, ethanol, and methanol, and the grinding is first coarsely ground to a particle size D 50 = 1-2 µm, and then finely ground to a particle size of 300-500 nm; the carbon source in step S2 is at least one of glucose, rock sugar, sucrose, fructose, polyethylene glycol, cyclodextrin, starch, and cellulose.
6. The preparation method according to claim 4, characterized in that The sintering temperature in step S3 is 675 - 780°C, and the time is 4 - 10 h; the inert atmosphere is at least one of nitrogen, argon, and helium; the mass content of carbon in the lithium iron manganese phosphate / carbon composite material is 1.2% - 2.0%.
7. The application of the preparation method according to any one of claims 1 - 3 or the preparation method according to any one of claims 4 - 6 in reducing impurities in the iron-manganese binary composite precursor and the lithium iron manganese phosphate / carbon composite material.
8. An iron-manganese binary composite precursor prepared by the preparation method according to any one of claims 1 - 3.
9. A lithium iron manganese phosphate / carbon composite material prepared by the preparation method according to any one of claims 4 - 6.
10. A battery, including a lithium iron manganese phosphate / carbon composite material prepared by the preparation method according to any one of claims 4 - 6.
Citation Information
Patent Citations
Preparation method of anode material LiMn1 / 3Fe2 / 3PO4 / C for lithium ion battery
CN104868123A
Preparation method for ferric manganese phosphate intermediate and lithium ferric manganese phosphate / carbon composite material
CN105244497A
Ferromanganese oxide precursor as well as preparation method and application thereof
CN119118087A
Lithium manganese iron phosphate precursor and preparation method of lithium manganese iron phosphate
CN119284859A